Investigation on Some Two Bidentate N,O-Schiff Base Ligands as Corrosion Inhibitors on Mild Steel in Sulfuric Acid Media - Baghaei, Fatemeh; Sheikhshoaie, Iran; Dadgarnezhad, Athareh (Asian Journal of Chemistry, 2016)
The effect of two bidentate Schiff bases 4-methoxy phenyl-N-salicylidine (M1) and 4-nitro-2-methoxy phenyle-N-salicylidine (M2) on mild steel surfaces in 0.5 M H2SO4 acid using electrochemical impedance and Tafel polarization techniques has been studied. Results obtained reveal that M1 and M2 compounds are good inhibitors for mild steel in 0.5 M sulfuric acid media. The inhibition is in both cases of mixed anodic-cathodic nature. Change in impedance parameters (Rt and Cdl) are indicative of adsorption of these two bidentate Schiff base ligands on metal surface leading to the formation of a protective film with inhibition efficiencies of around 93% at a concentration of 400 ppm at 25 ºC. The adsorption of M1 and M2 derivatives on the mild steel surface in sulfuric acid follows the Langmuir adsorption isotherm. In order to study the ability of quantum chemistry to select corrosion inhibitors, quantum chemical calculations have been applied to these bidentate Schiff base ligands. The corresponding structures have been optimized and the energies and symmetries of their molecular orbitals have been calculated using the semi-empirical AM1 semi-empirical methods. The theoretical results obtained have been compared with the experimental data and have a good agreement with the others.